Correlation chart of the Proterozoic assembly of the northeastern Canadian - Greenland Shield - Wardle, Richard J; Gower, C F; James, Donald T; St-Onge, Marc R; Scott, David J; Garde, Adam A; Culshaw, Nicholas G; van Gool, Jeroen AM; Connelly, James N; Perreault, Serge; Hall, Jeremy (Canadian Journal of Earth Sciences, 2002)
Chart 1: Correlation chart of the Proterozoic assembly of the northeastern Canadian Greenland Shield, including a location map and reference list.